Empowering the Disabled and Elderly: A Voice Control Unit for Assistive Technology - Karim, Shams Dhyaa; Al-Chalabi, Atheer Marouf M. (Iraqi Journal of Science, 2024)
The vast development of the technology of embedded systems has had a great impact on the healthcare field. Using low-cost, robust parts, this research proposes an innovative technology and design that enables paralyzed patients or elderly individuals to have a smart room with a voice recognition control unit that works like a joystick for various purposes. The aim is to create an environment that meets their needs and increases their independence, thereby improving their quality of life. The research will show the design of the control unit and present the various applications that can be programmed using voice commands, such as a wheelchair, bed, temperature, lights, TV, and alarm. The voice recognition module will be trained using the patient's voice, for example, to change the movement direction of a wheelchair. The system is based on training the Voice Recognition Module v3 with the use of Arduino and Node MCU. The results of the commendable accuracy of the English word response in a quiet environment ranged between 90% and 100% at the 0.2-meter distance and 50% and 100% at the 0.5-meter distance. While in a noisy environment, it ranged between 40% and 100% at the 0.2-meter distance and 10%–90% at the 0.5-meter distance. As for the Arabic-pronounced words, they ranged between 60% and 100% at the 0.2-meter distance and 30% and 100% at the 0.5-meter distance in a quiet environment. And, in a noisy environment, it ranged between 30% and 100% at the 0.2-meter distance and 10% and 100% at the 0.5-meter distance.